Natural (Fitri) Rhythm of the Holy Quran - Abolfazl Khoshmanesh (آموزه‌های قرآنی, 2019)
The relation between word and meaning is one of the subjects treated in different languages of which the language of the holy Quran. However, a point, neglected sometimes, is the physic of letters and its role in the general signification, the study and comparison of the similaries letters in some languages, attention to the role of human nature (fitra), being the common pillar of understanding in this field. This article considers the Holy Quran as a divine address to human nature fitra, and pays attention to its vocal signification for his interlocutors in different language, The article verifies too the examples of Quranic verses and some phrases in some other languages. At last, the article mentions the necessity, the utility and suggests a scientific analysis of the Quranic voices and to measure the datas regarding the Quranic signification.